ANALISIS DAYA SAING KOPRA DI MINAHASA SELATAN - Inra M. Lumintang; Tommy F. Lolowang; Lyndon R.J. Pangemanan (COCOS, 2015)
ABSTRACT  Inra Marsilia Lumintang. Competitiveness of Commodity Copra in South Minahasa Regency, under guidance  of Dr. Ir. Tommy F. Lolowang, MSi as a Chairman, Ir.Lyndon R.J. Pangemanan, ME as a Member.  The objective of this research is to know the competitiveness of commodities copra in the South Minahasa based on competitive advantage and comparative advantage. The benefitsofthis research isas reference material toSouthMinahasaregencygovernmentin formulatingpolicies relating tocopra commodity. Data used include primary data and secondary data.Primary data collectionconductedby interviewoncoprafarmers, especially farmers. While secondary datataken from theagenciesinvolved inthis researchasthe Central Bureauof Statistics, Department of AgricultureandPlantation, andIndustriesandTrade service. Determining the locationof this researchwas done by usingpurposiverandom sampling, where samplesweredetermined by consideringthe location ofa producer ofcoprain theSouth MinahasaRegency ofWestAmurang, su districtTewasen Villagewith10samples. The analysis usedin this research isDescriptiveAnalysis MethodsandPolicyAnalysisMatrix.  Keywords :Competitiveness, Comparative Advantage, Competitive Advantage.